1997
DOI: 10.21236/ada464965
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Multicast Transport and Integrated Erasure-Based Forward Error Correction

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…After the protocol description, we presented empirical results demonstrating overhead reduction and delay improvements resulting from MDP multicast parity-based repairing. These results compare well with previous analytical projections [Macker97a]. Finally, early NRL research and results regarding rate-based multicast congestion control were discussed.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…After the protocol description, we presented empirical results demonstrating overhead reduction and delay improvements resulting from MDP multicast parity-based repairing. These results compare well with previous analytical projections [Macker97a]. Finally, early NRL research and results regarding rate-based multicast congestion control were discussed.…”
Section: Discussionsupporting
confidence: 86%
“…In this section, we discuss a few experiments and summarize results. An earlier paper [Macker97a] presented analytical results predicting significant protocol improvements in efficiency for NACK-based reliable multicast when using proposed parity packet repairing methods. MDP now provides an implemented model of that proposal and an example empirical study was performed using protocol parameters similar to those used in the earlier analytical study.…”
Section: Some Test Results and Discussionmentioning
confidence: 99%
“…There are numerous and complex issues that must be addressed in wireless multicasting (e.g., see [4,15]). In this paper we focus on a single aspect of the multicasting problem, namely the incorporation of energy considerations into the construction of multicast trees and the choice of transmission power levels.…”
Section: Multicasting In Wireless Networkmentioning
confidence: 99%
“…Multiple forward error correction (FEC) approaches have been identified that can provide great performance enhancements to the repair process of NACK-oriented and other reliable multicast protocols [11], [12], [13]. NORM protocols can reap additional benefits since FEC-based repair does not _generally_ require explicit knowledge of repair content within the bounds of its coding block size (in symbols).…”
Section: Forward Error Correction (Fec)mentioning
confidence: 99%